2014
DOI: 10.1139/cjfas-2013-0460
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and habitat correlates of hybridization between hatchery and wild brook trout

Abstract: Human activities are breaking down barriers to interpopulation hybridization with results that range from populations that resist introgression to populations at serious risk of genetic extinction, particularly between wild and hatchery fish because of the routine stocking of lakes and streams containing wild populations. We investigated whether specific human actions and (or) habitat characteristics were associated with the extent of hybridization between hatchery and wild brook trout (Salvelinus fontinalis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 66 publications
1
38
0
Order By: Relevance
“…Potential wild‐hatchery introgression was identified based on the proportion of membership ( q ) to a genetic cluster associated with a hatchery strain, with q ≥ 0.10 used as a minimum. Prior studies have determined this threshold q ‐value to produce the highest proportion of correctly assigned pure and hybrid individuals (Vähä & Primmer, ) and have been previously used to examine hatchery introgression in Brook Trout (Harbicht et al, ; Humston et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential wild‐hatchery introgression was identified based on the proportion of membership ( q ) to a genetic cluster associated with a hatchery strain, with q ≥ 0.10 used as a minimum. Prior studies have determined this threshold q ‐value to produce the highest proportion of correctly assigned pure and hybrid individuals (Vähä & Primmer, ) and have been previously used to examine hatchery introgression in Brook Trout (Harbicht et al, ; Humston et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the degree to which hatchery introgression occurs can vary substantially. For Brook Trout, studies assessing stocked lakes have found moderate-to-high levels of hatchery introgression (Harbicht, Alshamlih, Wilson, & Fraser, 2014;Lamaze et al, 2012;Létourneau et al, 2017;Marie et al, 2010), whereas introgression in small stream systems is often limited (Bruce & Wright, 2018;Kelson, Kapuscinski, Timmins, & Ardren, 2015;White, Miller, Dowell, Bartron, & Wagner, 2018). This trend could be due to greater dispersal ability for Brook Trout stocked into streams, as fish can more easily move into neighboring tributaries, rather than remain confined to a single lake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive hybridization is especially problematic for fishes because there are limited pre‐ or postzygotic barriers to introgression among closely related taxa, and humans intentionally propagated and released staggering numbers of non‐native fish over the previous century (Gozlan, Britton, Cowx, & Copp, ). This is true for salmonids in the genera Oncorhynchus , Salmo , and Salvelinus , where widespread introductions for sportfishing and harvest have resulted in extensive introgression among populations and species (Allendorf & Leary, ; Araguas, Sanz, Pla, & García‐Marín, ; Escalante et al., ; Harbicht, Alshamlih, Wilson, & Fraser, ; Heath, Bettles, & Roff, ; Marie, Bernatchez, & Garant, ). Invasive hybridization in these taxa could be intensified by climate change, which is predicted to profoundly affect coldwater aquatic ecosystems by increasing stream temperatures, altering streamflow regimes, and increasing the frequency and severity of disturbance events, such as extreme drought and floods (Woodward, Perkins, & Brown, ), with substantial consequences for the spread of introduced salmonid species and their genes (Almodovar, Nicola, Ayllon, & Elvira, ; Comte & Grenouillet, ; Kelly, Whiteley, & Tallmon, ; Kovach, Muhlfeld, et al., ; Wenger et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive hybridization is especially problematic for fishes because there are limited pre-or postzygotic barriers to introgression among closely related taxa, and humans intentionally propagated and released staggering numbers of non-native fish over the previous century (Gozlan, Britton, Cowx, & Copp, 2010). This is true for salmonids in the genera Oncorhynchus, Salmo, and Salvelinus, where widespread introductions for sportfishing and harvest have resulted in extensive introgression among populations and species (Allendorf & Leary, 1988;Araguas, Sanz, Pla, & Garc ıa-Mar ın, 2004;Escalante et al, 2014;Harbicht, Alshamlih, Wilson, & Fraser, 2014;Heath, Bettles, & Roff, 2010;Marie, Bernatchez, & Garant, 2012).…”
Section: Introductionmentioning
confidence: 99%